A rigorous exploration of anal HPV genotypes using a next‐generation sequencing (NGS) approach in HIV‐infected men who have sex with men at risk for developing anal cancer - Chandrika J. Piyathilake; Suguna Badiga; Ranjit Kumar; Michael R. Crowley; Greer A. Burkholder; James L. Raper (Cancer Medicine)
Abstract Background There are no HPV‐based measures for managing anal cancer (AC) in HIV‐infected (HIV+) men who have sex with men (MSM) because of the high positivity of high‐risk (HR)‐HPVs. As next‐generation sequencing (NGS) is able to describe the composition of HPVs as percent (%) reads rather than positive vs negative results, we used NGS approach to detect HPVs in anal samples of HIV+ MSM to test its ability to differentiate those who are diagnosed with atypical squamous cells of unknown significance or greater (ASCUS+) from those who are free of such lesions and to understand the burden of HPV infections in relation to HPV vaccines. Methods Study included 81 HIV+ MSM characterized for demographics, patient‐reported outcome measures, HIV related laboratory measures and anal cytology. We summarized NGS HPV data using % read cut points (>0%‐>30%) and tested the relationship between % reads of HR‐HPVs and risk of ASCUS+ using logistic regression. Results Forty‐six HPVs were detected at the >0% read cut point. The prevalence of any HR‐HPVs varied from 100% to 40% with >0% to >30% reads while ≥99% were infected with HR‐HPVs included or not included in the 9 valent HPV vaccine at the >0% read cut point. MSM with >30% HR‐HPV reads were 4.5 times more likely to be diagnosed with ASCUS+ compared to ≤30% reads (P = .033). Conclusion NGS‐based approach is more accurate than PCR‐based HPV testing for identifying HIV+ MSM at risk for developing AC. We raise the concern regarding the efficacy of current HPV vaccines for preventing AC in this high‐risk population.